A196 INCIDENCE OF PEDIATRIC EOSINOPHILIC ESOPHAGITIS IN EDMONTON ZONE AND RISK OF STRICTURING AT DIAGNOSIS. (26th February 2020) - Burnett, D; Persad, R; Huynh, H Q
Abstract: Background: Eosinophilic esophagitis (EoE) is a common cause of esophageal dysfunction in children. A subset of children have a more severe phenotype of EoE, complicated by esophageal stricturing. Limited work has been done to characterize this phenotype. Aims: To determine the incidence of EoE, and the frequency of esophageal stricturing in pediatric EoE. Methods: We retrospectively identified all new cases of EoE at the Stollery Children's Hospital from 2015–2018 using esophageal biopsy reports for the province of Alberta (CoPath database), EoE clinic lists and an OR database for esophageal dilatation at the Stollery. Electronic medical records (EMR) were reviewed to confirm EoE diagnosis. For each confirmed case, clinical data was captured from the outpatient EMR and gastroscopy/pathology reports. A review of peri-endoscopy OR/nursing charts was performed on a subset of patients (n=75) to capture scope adverse event. Statistics Canada 2016 census data was used to calculate incidence rates. Results: 185 new cases of EoE were diagnosed at our center during the study period (see table). For patients < 15 years old living in Edmonton zone (n=73), the incidence over the 4 years was 11.1 cases per 100, 000 person years {8.7 (0–4 year-old), 7.6 (5–9 year old), and 18.1 (10–14 year old)}. There was limited variation in incidence in the 4 years (9.1–12.1 per 100, 000 person years). 8 of 185 (4%) patients had endoscopically confirmed esophageal strictures, 4 of which required mechanical dilation (mean 3.75 dilations per patient, range 1–6). 11/185 (5.9%) patients had more subtle signs of esophageal narrowing, but no strictures. No perforations or episodes of significant bleeding were reported in peri-endoscopy charts reviewed for 239 gastroscopes, including 16 dilations. Pain was reported after 15% of all scopes, including 50% of the 28 scopes with strictures and 63% of the 16 scopes involving dilations. Conclusions: Edmonton zone has one of the highest incidences of EoE reported in children. In this cohort, 4% had esophageal stricture (half required dilatation) and 5.9% had more subtle narrowing. Patients with strictures were older, had more frequent food impaction and longer duration of symptoms (Table). This data will be included in an ongoing multicenter case-control study across Canada. Funding Agencies: CAGWomen and Children's Health Research Institute (Univ. Alberta)